The Fourth Wave fights back: Deconstructing the Performativity of rape culture through contemporary Irish theatre, performance and society - QUIGLEY, CAROLE (Trinity College Dublin. School of Creative Arts. Discipline of Drama, 2019)
This dissertation seeks to examine and deconstruct contemporary rape culture. It explores, and builds on, the three preceding waves of the feminist movement, and contextualises established theories of hegemonic masculinity. It defines and explores what a 'rape culture' is in present times, and discusses how this culture has grown to infiltrate many aspects of society today. The thesis argues that we are currently in the fourth wave of the feminist movement, and it uses the lens of fourth wave feminist theory to interrogate the performance of contemporary rape culture. The thesis explores four main types of performance in a bid to highlight the ways in which this rape culture impacts on society as a whole. The first chapter looks at the performativity of language for women affected by sexual violence; focusing especially on the use of the words 'victim' or 'survivor' when describing a woman who has experienced such violence. It explores the performance and performativity of rape culture in everyday life and highlights how this culture directly impacts on the way women who have experienced sexual violence are treated by society. The second chapter looks at five Irish plays that have premiered between the years 2000 and 2016. All five plays contain a narrative of sexual violence against women. The narratives vary and include child sexual abuse, incestuous abuse, gang, or multiple perpetrator, rape and rape where the level of consent is questionable. The five plays are Gillian Greer's Petals, Marina Carr's On Raftery's Hill, Mark O'Rowe's Our Few and Evil Days and Caitriona Daly's Test Dummy. The respective plays are compared and contrasted to highlight how rape culture leads to the physical carrying out of acts of sexual violence. The theories of 'toxic femininity' and 'toxic masculinity' are used to explore this portrayal of sexual violence. The third chapter looks at contemporary beauty pageant performance, using the Rose of Tralee festival primarily, as an example of Irish pageant performance. The contest is deconstructed, and the presence of rape culture throughout is analysed. This chapter also examines external preconceptions of the festival. It uses Erica Murray and Oonagh O'Donovan's one-woman monologue play Oh! What A Lovely Rose! to analyse this external viewpoint. The fourth chapter focuses on Irish Dance performance, and how the child performer has becomes sexualised and objectified in the twenty-first century. This is due in part to the influence of American child beauty pageants on competitive dance performance and also as a result of the global success of both Riverdance and Lord of the Dance. It uses the 2017 Irish Dancing World Championships as a case study for examining the sexualisation and objectification of children throughout. The thesis as a whole seeks to interrogate the component parts of contemporary rape culture, including victim blaming, slut-shaming, rape myths, 'toxic femininity', 'toxic masculinity', online misogyny and internalised misogyny. It is a radical fourth wave feminist attempt to deconstruct this culture in order to move towards a more equal society for all. It is rooted in Irish performance and performativity, but due to the rise of social media and the fast-paced nature of information dissemination in the second decade of the twenty-first century, it is influenced by international popular culture performance. The dissertation unravels the falsehoods, misinformation and prejudicial preconceptions that surround and support rape culture.
APPROVED
Keywords: rape culture; feminism; fourth wave feminism; theatre; sexual violence; performativity; performance